COVID-19 Vaccines: Pakistan’s Perspective - Rahman, Sidra; Din, Misbahud; Khan, Sahrish; Yar, Lubna; Zia, Fatima; Idrees, Muhammad; Ali, Muhammad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
The pandemic of COVID-19 has affected millions of individuals around the globe. Its impact on the world has made essential progress in the research sector to develop safe and effective vaccines. Several vaccines for COVID-19 have been made utilizing the SARS-CoV-2’s spike protein. Presently, Moderna’s COVID-19 vaccine, Pfizer-BioNTech COVID-19 vaccine, and Johnson & Johnson’s Janssen vaccine are approved and suggested by CDC to prevent the COVID-19. Five vaccines (till April 2021) have been approved by WHO on emergency basis which are AstraZeneca, Pfizer-BioNTech, Moderna, Sinopharm, and Johnson & Johnson. The Food and Drug Administration approve the scientific standard of drugs and vaccine such as their efficacy, safety, and quality. Currently, ambiguous information regarding COVID-19 vaccine are being circulated globally. During health crisis, rumours roll out and generate fear, psychosis, and anxiety. On the other hand, the variants of SARS-CoV-2 are continuously emerging across the globe. Different platforms are being utilized for the development of whole virus-based vaccine, nucleic acid-based vaccine, and proteins sub-unit vaccine; all displayed good efficacy where few were further proceeded to clinical trials. The current article provide an overview on the COVID-19 vaccines, their efficacy, and discuss the possible reduction in vaccine efficacy due to the emergence of new variants.